Pengembangan Media Kartu Kuartet Berbasis Gambar 2 Dimensi Untuk Keterampilan Membaca Siswa Kelas II SD Negeri 15 Gunung Megang - Anisa Khoiril Latifah; Muhammad Idris; Mega Prasrihamni (Journal on Education, 2023)
The study aims to produce a two dimensional illustrative media development quartet card for reading skills, which have been tested and meet valid, practical, and effective criteria and can thus help students to master reading skills easily. The kind of research used was development research. The development model used in the research is the ADDIE model (Analyze, Design, Development, Evaluation) The subject in this study is the second graders of the elementary school at 15 Gunung Megang. The data on this study is generated from validation angkets, student responses figures, and demonstrative test of reading skills. The results from the angkett-based research team that assesses the quality of two-dimensional image and quartet card asa whole score 90.4% in a highly valid and usable category at the field test stage. Student responses score 94.25% in the highly practical category. The results of the demonstration test of the skill read of the entire student scored 86.17% in an excellent category. Based on data obtained, it could be concluded that a two-dimensional image quartet medium can be used asa primary school student learning medium